"Mummy, my eyelids are heavy": A case series of juvenile myasthenia gravis. Issue 2 (March 2021) - Krishna, Logeswari; Abdul Jalil, Nor Fadzillah; Lott, Pooi Wah; Singh, Sujaya; Choo, May May
Purpose: To report three cases of juvenile myasthenia gravis aged between 18 and 24 months with ocular symptoms as their first presentation. Method: A case series. Results: We present a case series of juvenile myasthenia gravis in a tertiary centre in Malaysia. Two of the three cases consist of a pair of twins who presented with ptosis of bilateral eyes; the first twin presented 4 months later than the second twin. These two cases were positive for anti-acetylcholine receptor antibodies and had generalized myasthenia gravis, whereas the other case was negative for receptor antibodies and was purely ocular myasthenia gravis. Conclusion: Juvenile myasthenia gravis is relatively rare in toddlers. Early diagnosis and commencement of treatment is important to slow the progression of the disease and avoiding life-threatening events.